Media Need Analysis of Learning Practicum in the Covid-19 Pandemic - Ika Wahyu Kusuma Wati; Anggri Sekar Sari; Widodo widodo; Rina Setyaningsih (Universitas Sultan Ageng Tirtayasa, 2020)
The Covid-19 pandemic has an impact on changing the learning model in Indonesia, from conventional learning to virtual learning. This causes a high gap in practicum learning. Where practicum learning that was originally in the laboratory can be applied at home. The purpose of this study was to determine the need for practical learning media for students. The research method used is descriptive quantitative. The research subjects were all UST PKK study program students. Determination of the sample through a purposive sampling of 77 respondents. The validity test of 31 statements about the instrument was declared valid. Meanwhile, all instruments were declared reliable with high reliability (0.705> 0.7). The total score averaged 87.35 which means it is highly expected. This result explained that the need for practical learning media using videos with clear instructions. So that further research needs to develop barcode-based e-job sheets according to the needs of learning media during the COVID-19 pandemic and the development of the digital generation era.